2015
DOI: 10.4172/psychiatry.1000251
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Evaluation: The Role of Treatment Fidelity within Psychosocial Interventions during the Last Decade

Abstract: Treatment fidelity is widely accepted as a critical component of successful psychological program implementation and treatment integrity. The current study is a critical interpretive synthesis of the review and evaluation literature on Treatment fidelity in psychosocial interventions in the last decade with an aim to explore the emphasis placed by researchers on: i) definitions of treatment fidelity; ii) different components of treatment fidelity; and iii) existing strategies to enhance treatment fidelity in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
(68 reference statements)
2
18
0
Order By: Relevance
“…Ensuring constructs are clearly labelled and differentiated from others is recommended for future work. A recent meta-evaluation of fidelity work in psychosocial intervention research supports our reviews’ findings as it found that there was strong variation in whether authors defined fidelity, that the use of different fidelity frameworks and terminology tended to generate confusion and make comparisons difficult, and that the operationalisation of receipt varied greatly [94]. The BCC framework was an attempt to build consistency in the science of fidelity, but ten years later this attempt does not appear to have been entirely successful.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Ensuring constructs are clearly labelled and differentiated from others is recommended for future work. A recent meta-evaluation of fidelity work in psychosocial intervention research supports our reviews’ findings as it found that there was strong variation in whether authors defined fidelity, that the use of different fidelity frameworks and terminology tended to generate confusion and make comparisons difficult, and that the operationalisation of receipt varied greatly [94]. The BCC framework was an attempt to build consistency in the science of fidelity, but ten years later this attempt does not appear to have been entirely successful.…”
Section: Discussionsupporting
confidence: 54%
“…The BCC framework was an attempt to build consistency in the science of fidelity, but ten years later this attempt does not appear to have been entirely successful. As was underlined by Prowse and colleagues [94] there is a need for standardisation in the field of fidelity, but this must not increase complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare provider behaviour change interventions (Slaughter et al, 2015) . Psychosocial interventions (Prowse & Nagel, 2015) . Physiotherapy behaviour change interventions (O'Shea et al, 2016) .…”
Section: Issues With Intervention Fidelitywhat Is Not Being Done Andmentioning
confidence: 99%
“…This failing in behavioral research needs attending to in future studies [36]. And when TF is measured, key recommendations in relation to good practice and consistency should be observed [37,38].…”
Section: Comparison With Other Programsmentioning
confidence: 99%
“…In the present investigation, all TF was measured via the 1-1 coded sessions, with supplementary observations carried out for the groups. Those carrying out research in MI groups should ensure that ongoing reflection, coding and supervision are fundamental components of interventions [37,38].…”
Section: Implications For Practitioner Trainingmentioning
confidence: 99%